Post-operative Analgesia with Intraperitoneal Bupivacaine Alone and with Dexmedetomidine Following Laparoscopic Cholecystectomy - Anees Ahmad; Ambreen Khan; Syed Shakeel Ahmed; Saima Noreen; Mohammad Idrees; Shahryar (Pakistan Journal of Medicine and Dentistry)
Background: Laparoscopic cholecystectomy (LC) is a customary treatment for patients with symptomatic cholelithiasis. This study aimed to compare the mean duration of analgesia (DOA) of intraperitoneal bupivacaine (BPV) with dexmedetomidine (DEX) to intraperitoneal BPV alone in patients undergoing LC.